2018
DOI: 10.1111/ggi.13314
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty on chronic pain, activities of daily living and physical activity in community‐dwelling older adults: A cross‐sectional study

Abstract: For community-dwelling older adults with frailty, chronic pain can negatively influence sensory, emotional and cognitive aspects of pain, leading to a decline in ADL and lower physical activity. Full pain assessment focused on sensory and emotional aspects of pain is important to identify frailty among older adults. Geriatr Gerontol Int 2018; 18: 1079-1084.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Although not analysed specifically in this study, other population studies have observed increased risk of disability with pain severity, frequency and multisite pain. 24,36 Given the complex interaction between pain, depression, frailty and disability, [37][38][39][40] future longitudinal studies with larger sample sizes may be needed to clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although not analysed specifically in this study, other population studies have observed increased risk of disability with pain severity, frequency and multisite pain. 24,36 Given the complex interaction between pain, depression, frailty and disability, [37][38][39][40] future longitudinal studies with larger sample sizes may be needed to clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Nakai et al reported that 42.7% of community-dwelling older adults had chronic pain, and chronic pain was associated with frailty and pre-frailty [3]. Hirase et al reported that 60.4% of community-dwelling older adults with frailty had chronic pain, and chronic pain was associated with negative emotional and cognitive aspects of pain, as well as a decline in activities of daily living (ADL) and lower physical activity levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases have been reported to create an adverse impact on the individual's ability to cope with life, by compromising quality of life and increasing financial costs [17]. Studies have reported that individuals aged 65 or over with chronic diseases have greater socioeconomic burdens and lower quality of life than those with no such diseases [18], that they experience more pain and restrictions [19], and that coping with life is therefore more difficult for them [20].…”
Section: Discussionmentioning
confidence: 99%